Air Quality Monitoring Technology and Its Benefits for Public Health in Indonesia - Ni Ketut Susilawati; Nurghany; Tiara Wirdadinaka; Zhafira Syarlianti Azzahra (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background : Air pollution is a global health threat, triggering respiratory and cardiovascular diseases, and even premature death. Urbanization, the increasing number of motorized vehicles, and industrial activity exacerbate pollution in densely populated areas. This situation demands an accurate, rapid, and accessible real-time air quality monitoring system to support public health prevention and protection. Objective: This study aims to review various air quality monitoring technologies that have been developed, and to analyze the benefits of their application in improving public health. Methods : A Systematic Literature Review (SLR) was conducted by collecting and analyzing articles from Google Scholar, following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. Articles published between 2020 and 2025 were reviewed using the keywords